Metal–organic frameworks under pressure - Collings, IE; Goodwin, AL (AIP Publishing, 2019)
Metal–organic frameworks (MOFs) are a broad and interesting class of materials known for their mechanical flexibility. As such, their response to pressure is usually extreme and often counterintuitive. This tutorial review surveys the structural response of MOFs to pressure as observed experimentally. It describes the experimental tools exploited in high-pressure crystallographic measurements and highlights some of the experiment design choices that influence the actual physics probed in these measurements. The main focus of the review is a description of the key pressure-driven structural responses exhibited by MOFs: isosymmetric compression, including negative compressibility; symmetry-lowering transitions; changes in connectivity; amorphization; and inclusion of the pressure-transmitting medium within the MOF pores. The review concludes both by highlighting some functional implications of these responses and by flagging some future directions for the field.